The Emergence of the Boston Ujima Project - Jimenez, Sarah. (2018)
Abstract: I document the emergence of the Boston Ujima Project, a project to develop a local politically organized economic ecosystem. My case study follows the first six months of activity, including an account of project efforts to design a participatory multi-stakeholder visioning process while simultaneously establishing an organizational structure and capacity to facilitate it. I situate the project in the context of a movement approach to societal transformation, identify and discuss specific transformative opportunities in the project, and then assess the activities of the first six months using the lens of prefigurative practice as a strategy for transformation.; Thesis (M.A.)--Tufts University, 2018.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Penn Loh.; Committee: Laurie Goldman.; Keyword: Urban planning.